2004
DOI: 10.1007/s00125-004-1372-0
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic islets from cyclin-dependent kinase 4/R24C (Cdk4) knockin mice have significantly increased beta cell mass and are physiologically functional, indicating that Cdk4 is a potential target for pancreatic beta cell mass regeneration in Type 1 diabetes

Abstract: Aims/hypothesis. Cyclin-dependent kinase 4 (Cdk4) is crucial for beta cell development. A mutation in the gene encoding for Cdk4, Cdk4R24C, causes this kinase to be insensitive to INK4 cell cycle inhibitors and induces beta cell hyperplasia in Cdk4R24C knockin mice. We aimed to determine whether this Cdk4R24C mutation also affects proper islet function, and whether it promotes proliferation in human islets lentivirally transduced with Cdk4R24C cDNA. Methods. Our study was conducted on wild-type and Cdk4R24C kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…Islet morphology is normal at birth, suggesting CDK4 is not required for pancreatic development, but islets fail to expand during postnatal growth. Conversely, mice expressing the INK-resistant mutant CDK4 `R24C' have hyperplastic islets due to increased postnatal beta cell proliferation [142, 143]. Mutation of the arginine at CDK4 position 24 is oncogenic in many tissues, despite also having impaired binding to D-cyclins and reduced efficacy as an Rb kinase [144].…”
Section: Evidence That Cdkn2a/b Influences Type 2 Diabetes Risk Via Bmentioning
confidence: 99%
“…Islet morphology is normal at birth, suggesting CDK4 is not required for pancreatic development, but islets fail to expand during postnatal growth. Conversely, mice expressing the INK-resistant mutant CDK4 `R24C' have hyperplastic islets due to increased postnatal beta cell proliferation [142, 143]. Mutation of the arginine at CDK4 position 24 is oncogenic in many tissues, despite also having impaired binding to D-cyclins and reduced efficacy as an Rb kinase [144].…”
Section: Evidence That Cdkn2a/b Influences Type 2 Diabetes Risk Via Bmentioning
confidence: 99%
“…Knockout studies have shown a very specific phenotype, with beta-cell hypoplasia and severe diabetes [191, 194, 245], whilst studies using an activating mutation in CDK4, rendering it resistant to p16, have resulted in pancreatic hyperplasia, which demonstrated normal physiology [191, 192]. Other studies have shown up to a three-fold increase in beta-cell proliferation with CDK4 overexpression [191, 193].…”
Section: Postnatal Beta-cell Regulationmentioning
confidence: 99%
“…35,75 Murine β-cells express abundant cdk-4 and cyclin D2, and genetic mouse models have shown them to be critical for β-cell proliferation and diabetes development. [76][77][78][79] In contrast, human β-cells contain high levels of the analogous enzyme cdk-6, and cyclins D1 and D3 are thought to play a role. Recently, it was reported that overexpression of cdk-6 and cyclin D1 in isolated human β-cells in vitro induced BrdU incorporation and Ki67 expression.…”
Section: Disclosure Of Potential Conflicts Of Interestmentioning
confidence: 99%